2019
DOI: 10.1016/j.ajpath.2019.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone Acetate Prevention of Cervical Cancer through Progesterone Receptor in a Human Papillomavirus Transgenic Mouse Model

Abstract: Cervical dysplastic lesions called cervical intraepithelial neoplasias (CINs) need be treated to prevent cervical cancer. Currently available surgical procedures are effective, but the development of noninvasive treatment is warranted. In human papillomavirus transgenic mice engineered to express human papillomavirus type 16 E6 and E7, short-term treatment with 17b-estradiol induces CINs that progress to cervical cancer if the treatment is continued. In the present study, this mouse model was used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…20,23 PR has also been reported to play a role in the prevention of cervical carcinogenesis in mice tests. 11,24 However, PR was not associated with LNM and survival in the current study, which may be because PR only functions in the early stage of carcinogenesis.…”
contrasting
confidence: 69%
“…20,23 PR has also been reported to play a role in the prevention of cervical carcinogenesis in mice tests. 11,24 However, PR was not associated with LNM and survival in the current study, which may be because PR only functions in the early stage of carcinogenesis.…”
contrasting
confidence: 69%
“…10 In a human papillomavirus transgenic mouse model, medroxyprogesterone acetate prevented cervical dysplastic lesions from progressing to invasive cancer by inhibiting cell proliferation and promoting apoptosis. 11 P4 also inhibits the growth of pancreatic adenocarcinoma cells by modulating the expression of proliferation-related genes. 12 We previously demonstrated that expression of membrane progesterone receptor alpha (mPRα) was significantly down-regulated in breast cancer tissue of patients with tumor-metastasis-node (TMN) stage 4 disease compared to those at TNM 1-3.…”
Section: Introductionmentioning
confidence: 99%
“…P4 has been shown to interfere with the cell cycle of prostate stromal cells and suppress their proliferation, 9 cell migration and invasion 10 . In a human papillomavirus transgenic mouse model, medroxyprogesterone acetate prevented cervical dysplastic lesions from progressing to invasive cancer by inhibiting cell proliferation and promoting apoptosis 11 . P4 also inhibits the growth of pancreatic adenocarcinoma cells by modulating the expression of proliferation‐related genes 12 .…”
Section: Introductionmentioning
confidence: 99%